2020
DOI: 10.1136/archdischild-2020-318978
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of death in extremely preterm infants in the Netherlands

Abstract: ObjectiveIn the Netherlands, the threshold for offering active treatment for spontaneous birth was lowered from 25+0 to 24+0 weeks’ gestation in 2010. This study aimed to evaluate the impact of guideline implementation on survival and causes and timing of death in the years following implementation.DesignNational cohort study, using data from the Netherlands Perinatal Registry.PatientsThe study population included all 3312 stillborn and live born infants with a gestational age (GA) between 240/7 and 266/7 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Mortality was also lower and time to death longer in our cohort than reported in a recent cohort from the Netherlands. 22 Mortality details have implications for parental guidance: in 1996 one could tell parents that if their child survived 3 days, the chances for ongoing survival were high, whereas in our present cohort, the period of uncertainty regarding ultimate outcome is prolonged and has the potential to increase parental stress.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Mortality was also lower and time to death longer in our cohort than reported in a recent cohort from the Netherlands. 22 Mortality details have implications for parental guidance: in 1996 one could tell parents that if their child survived 3 days, the chances for ongoing survival were high, whereas in our present cohort, the period of uncertainty regarding ultimate outcome is prolonged and has the potential to increase parental stress.…”
Section: Discussionmentioning
confidence: 79%
“…Overall mortality was lower than expected, at 12% within the initial hospitalization, with an additional 1% who died between 9 and 25 months after birth. 9,[21][22][23] As expected, the risk of death was highest in the least mature infants; however, the ability of GA to who survived to be enrolled, so this difference is accentuated. Mortality was also lower and time to death longer in our cohort than reported in a recent cohort from the Netherlands.…”
Section: Discussionmentioning
confidence: 94%
“…However, preferences concerning the upper threshold for offering comfort care still greatly diverge, as well as practices such as offering a cesarean section and providing cardiopulmonary resuscitation (13). Finally, a recent study by van Beek et al shows that the implementation of the 2010 guideline "resulted in increased neonatal intensive care unit admission rates and postnatal survival" (14). Although these results are useful to reflect on the guideline, more follow-up research on longer term outcomes is required.…”
Section: The History Of Dutch Guidelines On Treatment At the Edge Of Viabilitymentioning
confidence: 99%
“…15 Therefore, comparing incidences to other countries is challenging as neonatal policies, survival and screening criteria may differ. Survival for infants born at 24 weeks (as % of live borns) was 34.4% in the Netherlands in the period 2011-2017 16 . Other similar national population-based cohorts report however survival rates varying from 31% to 67% in 24-week infants.…”
Section: Clinical Sciencementioning
confidence: 99%
“…Although survival of extremely premature infants in the Netherlands is still in the lower range compared with other high income countries, with continuously improving survival of these neonates, awareness of concomitant conditions such as (severe) ROP remains crucial. 16 Second, surprisingly the NEDROP 1 revealed that the ETROP criteria, 7 which apply since their publication in 2004, were not yet fully implemented in the Netherlands. 4 The former guideline dating from 1997 did not include a directive on ROP treatment, therefore possibly, utilisation into practice stayed behind.…”
Section: Clinical Sciencementioning
confidence: 99%